2006
DOI: 10.1093/toxsci/kfl119
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Activation Impairs Extracellular Matrix Remodeling during Zebra Fish fin Regeneration

Abstract: Adult zebra fish completely regenerate their caudal (tail) fin following partial amputation. Exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) inhibits this regenerative process. Proper regulation of transcription, innervation, vascularization, and extracellular matrix (ECM) composition is essential for complete fin regeneration. Previous microarray studies suggest that genes involved in ECM regulation are misexpressed following activation of the aryl hydrocarbon receptor. To investigate whether TCDD bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 68 publications
2
49
0
Order By: Relevance
“…Instead, it appeared that TCDD may activate pathways leading to collagen degradation in CCl 4 -treated mice, based on increased collagenase activity and possibly increased MMP-13 activity in the liver of CCl 4 /TCDD-treated mice. These findings corroborate other studies in which TCDD was reported to increase expression of the collagenase MMP-13 in zebrafish and cell culture (Andreasen et al , 2006; Andreasen et al , 2007). It is possible that TCDD directly activates MMP-13 gene expression, based on the identification of a consensus XRE in the promoter region of the zebrafish MMP-13 gene (Andreasen et al , 2006) as well as in the mouse MMP-13 gene (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…Instead, it appeared that TCDD may activate pathways leading to collagen degradation in CCl 4 -treated mice, based on increased collagenase activity and possibly increased MMP-13 activity in the liver of CCl 4 /TCDD-treated mice. These findings corroborate other studies in which TCDD was reported to increase expression of the collagenase MMP-13 in zebrafish and cell culture (Andreasen et al , 2006; Andreasen et al , 2007). It is possible that TCDD directly activates MMP-13 gene expression, based on the identification of a consensus XRE in the promoter region of the zebrafish MMP-13 gene (Andreasen et al , 2006) as well as in the mouse MMP-13 gene (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…For the adult in situ hybridization study, 2-month-old AB strain zebrafish were used. The fin amputations were performed as previously described (15,16,20,21). The Tg(hsp70l:tcf3-GFP) line was obtained from ZIRC.…”
Section: Methodsmentioning
confidence: 99%
“…Considering previous studies showing that AhR activation in mouse causes inflammatory skin lesions (Tauchi et al, 2005) and impairs fin regeneration in zebra fish (Andreasen et al, 2007), and since humans exposed to dioxin develop the skin disease chloracne associated with an increase in AhR-dependent transcription (Tang et al, 2008), we first analyzed whether AhR expression modulates wound healing in vivo. Histological analyses of wounds performed in the dorsal skin of Ahr +/+ and Ahr -/-mice revealed that AhR-null mice closed their wounds significantly faster than wild-type mice, this effect being more pronounced between days 3 and 5 (wound diameter was measured as the distance between both flanks of the regenerating neo-epithelium or granulation tissue) (Fig.…”
Section: Loss Of Ahr Expression Improves Wound Healing By Acceleratinmentioning
confidence: 99%
“…A recent report showed that constitutive activation of AhR and increased expression of Cyp1a1, Gsta1, Fos and TGFA are underlying factors in the development of chloracne in human subjects occupationally or accidentally exposed to significant doses of polycyclic aromatic hydrocarbons (Imamura et al, 2007;Tang et al, 2008). Regeneration studies in adult zebra fish have revealed that AhR2 activation by acute exposure to dioxin (TCDD,2,3,7,dioxin) impairs caudal (tail) fin regeneration (Andreasen et al, 2007), which suggests that AhR has an inhibitory role in tissue remodeling. Finally, transgenic mice expressing a constitutively activated form of AhR in their keratinocytes develop severe skin lesions with itching and inflammation that resembled atypical atopic dermatitis (Tauchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%